In vivo imaging of colitis and colon cancer development in mice using high resolution chromoendoscopy. Issue 7 (10th June 2005) - Becker, C; Fantini, M C; Wirtz, S; Nikolaev, A; Kiesslich, R; Lehr, H A; Galle, P R; Neurath, M F
Abstract : Background: Mouse models of colitis and cancer are indispensable for our understanding of the pathogenesis of these diseases. In the past, mice had to be sacrificed in order to analyse colitis activity and tumour development. We have developed a safe method for high resolution endoscopic monitoring of living mice. Methods: Mice developing colitis or colonic tumours were anaesthetised using avertine and repeatedly examined by endoscopy. A novel miniendoscope (1.9 mm outer diameter), denoted Coloview, was introduced via the anus and the colon was carefully insufflated with an air pump before analysis of the colonic mucosa. An extra working channel allowed the introduction of biopsy forceps or injection needles as well as surface staining with methylene blue in order to visualise the surface of the crypts and the pit pattern architecture. Results: Endoscopic pictures obtained were of high quality and allowed monitoring and grading of disease. Scoring of colitis activity as well as tumour size and growth was possible. In addition, pit pattern analysis using chromoendoscopy permitted discrimination between inflammatory and neoplastic changes. Biopsies yielded enough tissue for molecular and histopathological analyses. Conclusions: In summary, chromoendoscopy in mice allows monitoring of the development of colitis and colon cancer with high resolution. Manipulations such as local injection of reagents or taking biopsies can be performed easily.